Molecular mechanical studies of proflavine and acridine orange intercalation. - Dearing, A (1981)
Previous workers have reported that proflavine and acridine orange form various structurally different complexes with the dinucleoside phosphates rCpG and dCpG, with uniform C3'-endo and mixed C3'-endo (3'-5') C2'-endo sugar puckers being observed. We present theoretical calculations, based on the method of molecular mechanics, which support the experimental observations. The results suggest that the mixed C3'-edo (3'-5') C2'-endo pucker conformation isi intrinsically more stable than the uniform C3'-endo conformation, but that the additional stabilisation gained from specific, hydrogen bonding, interactions between nucleic acid and solvent, or intramolecularly within the nucleic acid, can lead to the adoption of the latter conformation, or of variants between the two. The role played by hydrogen bonding between amino-groups and nucleic acid phosphate appears more subtle than previously supposed.